What Entrepreneurial Followers at the Start-Up Stage Need From Entrepreneurship Cultivation: Evidence From Western China - Dong, Xuefan; Tang, Chengxiang; Lian, Ying; Tang, Daisheng (Frontiers in Psychology, 2019)
Entrepreneurial followers are defined as the crucial members of a specific entrepreneurial team and do not include the leader or normal employees in the present paper. This population can be viewed as indispensable factors in the success of entrepreneurship, especially in the start-up stage. In addition, according to the following time, they can be divided into two groups, namely long-term entrepreneurial followers and short-term entrepreneurial followers. However, studies focusing on entrepreneurship cultivation for entrepreneurial followers are relatively few. The main purpose of this paper is to determine the needs of Chinese entrepreneurial followers in entrepreneurship cultivation from the early stage of entrepreneurship. In this paper, a sample of 200 long-term entrepreneurial followers from Tianfu New Area in China was investigated. To enable the researchers to explore the unique opinions of entrepreneurial followers, a mixed data collection approach that combined interviews and questionnaires was chosen in this study. The results revealed following findings: (a) high levels of social capital, good entrepreneurial opportunities and projects, and highly cooperative teams were viewed as the most important factors for entrepreneurship by entrepreneurial followers in China; (b) most entrepreneurial followers believed that the primary difficulty in the cultivation process was the inefficiency in talent training mechanism; and (c) nearly 40% of samples suggested that the cultivation and enhancement of local talents should be firstly carried out by the Chinese government, indicating a gap between the supporting force for local and returned talents in China. In addition, various types of incentive policies and good environments for talent growth were also considered as important suggestions by entrepreneurial followers. We found that unlike entrepreneurial leaders, entrepreneurial followers focus more on income expectation, and personal development rather than supporting the development of companies in China. These findings should be viewed as priorities when enhancing current entrepreneurship cultivation in China.